Robust statistics towards detection of the 21 cm signal from the Epoch of Reionization - Trott, Cathryn; Fu, Shih Ching; Murray, Steven; Jordan, Chris; Line, Jack; Barry, N.; Byrne, R.; Hazelton, B.J.; Hasegawa, K.; Joseph, R.; Kaneuji, T.; Kubota, K.; et al. (OXFORD UNIV PRESS, 2019)
© 2019 The Author(s) Published by Oxford University Press on behalf of the Royal Astronomical Society.